Choose me - Gerritsen, Tess; Braver, Gary (Thomas & Mercer, 2021)
"Taryn Moore is young, beautiful, and brilliant, so why would she kill herself? When Detective Frankie Loomis arrives on the scene ... she knows in her gut there's more to the story ... To English professor Jack Dorian, Taryn was the ultimate fantasy: intelligent, adoring, and completely off limits. But there was also a dark side to Taryn, a dangerous streak that threatened those she turned her affections to, including Jack. And now that she's dead, his problems are just beginning"--